2017
DOI: 10.9789/2175-5361.2017.v9i3.627-633
|View full text |Cite
|
Sign up to set email alerts
|

Análise do perfil sociodemográfico de notificados para hepatite B e imunização contra a doença Sociodemographic analysis of reported hepatitis B and immunization against the disease

Abstract: Objetivo: Analisar o perfil sociodemográfico dos notificados para hepatite B e a imunização contra a doença. Métodos: Estudo com dados de notificação de hepatite B na vigilância epidemiológica de município de Minas Gerais, entre 2007 a 2015, conduzido no Programa de Educação pelo Trabalho para a Saúde. Estatística descritiva e analítica, com nível de significância p<0,05.  Resultados: Notificou-se 132 casos; dois óbitos. A idade dos notificados variou de zero a 87 anos, média de 35,8 (±14,0) anos. Maior fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…A study carried out in Minas Gerais, including people aged 60 or over, found a decrease in cases of hepatitis B from 2007 onwards. However, they highlight that among the reported cases, most individuals had not been immunized or had an incomplete vaccination schedule for hepatitis B (24) . In Brazil, in 2016 the offer of the hepatitis B vaccine was extended to all population groups, regardless of age group or vulnerable condition, especially older adults, who with the increase in life expectancy and the rise of sexual activity without safe practices are exposed to the risk of acquiring sexually transmitted infections (25) .…”
Section: Discussionmentioning
confidence: 97%
“…A study carried out in Minas Gerais, including people aged 60 or over, found a decrease in cases of hepatitis B from 2007 onwards. However, they highlight that among the reported cases, most individuals had not been immunized or had an incomplete vaccination schedule for hepatitis B (24) . In Brazil, in 2016 the offer of the hepatitis B vaccine was extended to all population groups, regardless of age group or vulnerable condition, especially older adults, who with the increase in life expectancy and the rise of sexual activity without safe practices are exposed to the risk of acquiring sexually transmitted infections (25) .…”
Section: Discussionmentioning
confidence: 97%
“…Destarte, de acordo com Gusmão et al, desconhecimento sobre a patologia e a baixa escolaridade percebida são fatores relacionados à falta de adesão à vacina e as medidas preventivas das doenças (12).…”
Section: Resultsunclassified
“…Atenção especial deve ser dada às adolescentes, as quais apresentam maior relato de vergonha em portar o preservativo, aumentando a vulnerabilidade feminina (11). O fato de residir em zona com restrição ao aprendizado, culmina em baixa escolaridade, ocasionando um efeito cascata de menor adesão à imunização e, em consequência, menor proteção à infecção pela hepatite B (12).…”
Section: Introductionunclassified
“…It is known that besides the use of condoms and not sharing syringes and other perforating objects, vaccination is the most efficient and safest way to prevent hepatitis B. 17 Pregnant women were more likely to have positive markers for HBV (HBsAg and Total Anti-HBc). The rate of HBV infection in women in Brazil is high, the sex ratio is almost 1:1, making the infection in pregnant women high -prevalence of 11.1% (23,563 cases).…”
Section: Discussionmentioning
confidence: 99%